Pengaruh Metode 5’S (Swaddling, Side/Stomach Position, Sushing, Swinging dan Sucking) terhadap Penurunan Nyeri Pada Bayi Setelah Imunisasi Dasar - Rahmaini Fitri Harahap; Desi Hernida; Naqia Mahfudhah; Nellina Khartati; Nelli Herayani (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2021)
Immunization that is injected into the baby's body can cause pain or pain in the baby. The pain experienced by infants during immunization is an emotional experience that makes the baby uncomfortable because of the damage to the tissues in the baby's body. The purpose of this study was to determine the effect of the 5'S method (Swaddling, Side/Stomach Position, Sushi, Swinging and Sucking) on reducing pain in infants after basic immunization injections. This research method uses a quasi-experimental, using a research design of One Group Pre-test and Post-test without a control group. The sample used in this study was the entire population (total sampling), namely mothers who came for immunization in November as many as 33 babies. The statistical test used in this study using the Wilcoxon test, used to see the effect between two variables with a 95% confidence degree. The results of this study were the response to pain in infants after basic immunization injections before the 5'S method was carried out, the majority experienced severe pain. There was a decrease in pain in infants after basic immunization after the 5'S method the majority experienced moderate pain. The conclusion that the 5'S method is effective in reducing the pain response of infants aged 0-4 months when immunization injection is performed is based on the concept that 4 months after birth, the baby is not fully ready to be outside the womb, the baby longs for a comfortable sensation like being in the womb. Suggestions for the Puskesmas are that it is hoped that the results of this study can be taken into consideration in making SOPs (Standard Operatinal Procedures) in calming babies and can socialize to mothers, that 5'S actions are very beneficial for babies and explain the negative effects of pain and crying that are not treated immediately.Keywords: 5’s, painful, immunization